2020
DOI: 10.1108/ijchm-05-2020-0443
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities with H-2B visas: can luxury resorts survive without them?

Abstract: Purpose This study aims to provide a deeper look into why luxury resorts engage in the H-2B visa program and the opportunities and challenges from the human resources employee perspective. Adequate staffing is a well-documented challenge for luxury resorts due to their location, seasonality and access to qualified labor. Many resorts turn to the H-2B non-immigrant visa to mitigate the issue. Design/methodology/approach This study consists of in-depth interviews with human resource employees. An additional su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Recent research suggested that in the ongoing pandemic, hygiene and sanitation factors influence consumer’s decisions pertaining to accommodations (Gossling et al , 2020). Hygiene factors also include safety compliance measures as directed by health-care and workplace safety authorities (Kubickova and Neal, 2000). All hotels have adopted their own standard operating procedures to maintain high standards of hygiene.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research suggested that in the ongoing pandemic, hygiene and sanitation factors influence consumer’s decisions pertaining to accommodations (Gossling et al , 2020). Hygiene factors also include safety compliance measures as directed by health-care and workplace safety authorities (Kubickova and Neal, 2000). All hotels have adopted their own standard operating procedures to maintain high standards of hygiene.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, our main intention with the questionnaire was to reach the largest number of Omani employees who could not be reached through focus groups, so that they could have the opportunity to express their opinions on the various themes of the study. This data collection approach was recently employed by researchers in the field of hospitality for similar purposes (see for example, Kubickova and Neal, 2020). The questionnaire contained three sections.…”
Section: Methodsmentioning
confidence: 99%
“…For example, mask-wearing, social distancing, limits on gathering and temporary business closures were required in many destinations, forcing hotels to redesign the customer experience and its delivery, often costly and labor-intensive, transforming hotel employees from frontline workers to essential employees (Rivera, 2020). Before COVID-19, hotel employees were already facing persistent labor shortages, low pay, long working hours, shift work, difficult customers and limited opportunities for career advancement contributing to a stressful working environment (Kubickova & Neal, 2020). Again, during COVID-19, they were dealing with potential health and safety risks while being expected to instill trust and confidence in their customers (Rivera, 2020;Stergious & Farmaki, 2021).…”
Section: Introductionmentioning
confidence: 99%